LGBT (Lesbian, Gay, Bisexual, Transgender) Dilihat Dari Sudut Pandang Undang-Undang HAM Di Indonesia - Imanuel Robert Tanoko (Widya Yuridika, 2022)
Everyone is born to be a different person. Likewise, everyone's sexual orientation is different. This makes everyone have freedom as long as they do not go against the laws and regulations and harm others. But in Indonesia not all people can accept the existence of LGBT people, mostly reject it. LGBT itself is known as lesbian, gay, bisexual, and transgender. No human being can be discriminated, while many LBGT people are discriminated, like being ostracized. In this case, LGBT also have human rights. Based on the Universal Declaration of Human Rights, it regulates freedoms such as race, color, sex, language, religion, politics or other views, national or social origin, property rights, birth or other status. Indonesia regulates discrimination, based on article 1 paragraph 3 of Law Number 39 of 1999 concerning Human Rights explaining discrimination, which states that everyone is free from discrimination. Indeed, there is no expliction regarding regulations for LGBT people, only a few regions have issued regional regulations regarding LGBT, one of which is the Musi Banyuasin Regional Regulation which prohibits LGBT. The regulation is contrary to the existence of human rights. Where it is not permissible to discriminate against every human being, as long as it does not harm other people and everyone has the freedom to choose what they want..